DYKES ON PERMAFROST, KELSEY GENERATING STATION, MANITOBA - Johnston, G. H. (Canadian Geotechnical Journal, 1969)
Performance studies of two major, but relatively small (2000-ft (~610m) long, maximum height 20 ft (6.1 m)), sand dykes constructed on perennially frozen ground were initiated in 1958 at the Kelsey Generating Station of Manitoba Hydro on the Nelson River. Permafrost occurred under these dykes in scattered islands or patches of variable thickness and size.Preliminary analyses, though only approximate, indicated that within a 50-year period significant thawing would occur beneath the dyke–water interface and that the permafrost under the reservoir would thaw completely. Ground settlements of as much as 6 ft (1.8 m) were to be expected as thawing took place. To check the estimated performance, field instrumentation was installed and an observational program begun in 1959.A distinct pattern of thawing and settlement each year has been observed. Major thawing and settlement occur during the summer months at rates that are greater than those experienced during the winter. The change in rate of thaw (and thus also the rate of settlement, which is partly a function of thawing) is directly connected with the change in water temperature or rate of heat flow into the ground.